1994
DOI: 10.1063/1.357174
|View full text |Cite
|
Sign up to set email alerts
|

Growth and structure of rapid thermal silicon oxides and nitroxides studied by spectroellipsometry and Auger electron spectroscopy

Abstract: Rapid thermal oxidation of Czochralski-grown silicon in either O2 or N2O atmospheres have been studied using spectroellipsometry and Auger electron spectroscopy. Multiwavelength ellipsometric data were processed in order to separately derive the thicknesses and refractive indexes of rapid thermal dielectrics. Results revealed a significant increase of the mean refractive index as the film thickness falls below 20 nm for both O2 or N2O oxidant species. A multilayer structure including an about 0.3-nm-thick inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Similar reservations have been recently raised in a study on the sensitivity of the measured oxide thickness on ellipsometry parameters [6]. In [4], it was suggested that 0741-3106/97$10.00 © 1997 IEEE the refraction index could change from 1.4 for thick oxides to 1.7 for oxides thinner than 100Å. Based on our data, 1.458 is still valid for thin oxides down to 25Å.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Similar reservations have been recently raised in a study on the sensitivity of the measured oxide thickness on ellipsometry parameters [6]. In [4], it was suggested that 0741-3106/97$10.00 © 1997 IEEE the refraction index could change from 1.4 for thick oxides to 1.7 for oxides thinner than 100Å. Based on our data, 1.458 is still valid for thin oxides down to 25Å.…”
Section: Resultssupporting
confidence: 68%
“…The averaged values from ellipsometry (TEM) are 25 (26), 38 (38), 76 (79), 96 (97), 123 (123), and 144Å (146Å). This indicates that previous suggestions of substantial changes in the oxide index of refraction [4] should be reexamined. Similar reservations have been recently raised in a study on the sensitivity of the measured oxide thickness on ellipsometry parameters [6].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Another way to view this situation is that the measured changes are optically dominated by the overlayer. It is interesting to consider a recent article 27 where SE and Auger spectroscopy were used to characterize nitrided oxides. The SE measurements were done in air and nitrided oxides were prepared by rapid thermal oxidation in N 2 O at temperatures up to 1200°C.…”
Section: Resultsmentioning
confidence: 99%
“…µÏÇÐßÛÇÐËÇ ÕÑÎÜËÐÞ ÑÕ 8 AEÑ 2 ÐÏ ÔÑÒÓÑÄÑÉAEÂÇÕÔâ ÖÄÇÎËÚÇÐËÇÏ ÒÑÍÂÊÂÕÇÎâ ÒÓÇÎÑÏÎÇÐËâ ÑÕ 1,52 AEÑ 2,0. ±ÑAEÑÃÐÞÌ à××ÇÍÕ ÐÂÃÎá-AEÂÎÔâ ÓÂÐÇÇ ¤ÑÐÑÐÑÏ Ô ÔÑÂÄÕÑÓÂÏË [13].¯Â ÓËÔÖÐÍÇ 2 6 ÊÄÇÐßÇÄ, n 1,57 [18,19] ²ËÔ. 14.…”
mentioning
confidence: 99%